X-1+5x-3+5x-3=

Simple and best practice solution for X-1+5x-3+5x-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-1+5x-3+5x-3= equation:


Simplifying
X + -1 + 5x + -3 + 5x + -3 = 0

Reorder the terms:
-1 + -3 + -3 + X + 5x + 5x = 0

Combine like terms: -1 + -3 = -4
-4 + -3 + X + 5x + 5x = 0

Combine like terms: -4 + -3 = -7
-7 + X + 5x + 5x = 0

Combine like terms: 5x + 5x = 10x
-7 + X + 10x = 0

Solving
-7 + X + 10x = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + X + 7 + 10x = 0 + 7

Reorder the terms:
-7 + 7 + X + 10x = 0 + 7

Combine like terms: -7 + 7 = 0
0 + X + 10x = 0 + 7
X + 10x = 0 + 7

Combine like terms: 0 + 7 = 7
X + 10x = 7

Add '-10x' to each side of the equation.
X + 10x + -10x = 7 + -10x

Combine like terms: 10x + -10x = 0
X + 0 = 7 + -10x
X = 7 + -10x

Simplifying
X = 7 + -10x

See similar equations:

| 6+6r=18 | | 9+9m=-9+6m+5m | | -16=30x+15x^2 | | 6x-15x=18 | | -2x-39=-6x+29 | | 6a+4a-3a= | | 63x^8=0 | | 4k+ar=r-7y | | -3(t-5)+5t=7t-4 | | X^2+6x-1=7x-9 | | -4.19+11.5c=10c-0.87+1.7c | | 6x+3x-6=10x+5 | | -8-5v=-9v | | -4y+8z=32 | | -5-8a=-45 | | X+6=5(2x-2) | | y(x^2+y^2)dx=x^3dy | | -2-10w=4-8w | | r=9.6 | | 14+12w=16+9w | | -11(4+k)=220 | | 15x(-2-x)-12=4 | | (3.14)x^2=28.26 | | 3q-2=7 | | -8m=4 | | 6r+10=124 | | -2b+6-4=18 | | -6u=10-5u | | 5.9s=3(-3.4s-15.91) | | 5x+6=16x+-3x+54 | | x-10=104 | | -3(8+n)=33 |

Equations solver categories